EP209/#686 BCAM-AKT2 fusion protein and the IGF1 signaling pathway in epithelial ovarian cancer. (4th December 2022) - Khazem, Hala; Reder, Dvir; Sharon, Shilhav Meisel; Hantisteanu, Shay; Mordechai, Hallak; Werner, Haim; Bruchim, Ilan
Abstract : Objectives: The IGF axis has been identified as an important molecular pathway in the development of epithelial ovarian cancer (EOC); hence mutations or fusion genes associated with the IGF axis are candidates to play a role in diagnosis and treatment. A constitutively active fusion protein BCAM-AKT2 was recently identified in high grade serous ovarian carcinoma. We aim to investigate the role of BCAM-AKT2 fusion protein in the IGF1 signaling pathway in EOC and whether it influences ovarian cancer cell proliferation and activity. Methods: In-vitro experiments were established in HGSC cell lines. RNA was extracted from BCAM-AKT2 transfected cells and expression levels of altered genes were validated by qRT-PCR experiments. Protein expression levels of BCAM-AKT2, IGF1R, and the downstream key factors were measured by western blots. XTT assay was used to measure the effect of the BCAM-AKT2 fusion protein on proliferation and biological activity of EOC cell lines. Results: Overexpression of BCAM-AKT2 in EOC cells resulted in alterations of several genes which exhibit tumor-promoting properties (CYBB (NOX2), NPY). qRT-PCR validation experiments confirmed that the NPY gene was highly expressed in BCAM-AKT2 transfected cells, while CYBB (NOX2) expression levels showed ambiguous results. Moreover, XTT assays suggest that BCAM-AKT2 induces proliferation in EOC cell lines. Conclusions: Implications: Our results suggest a possible effect of the BCAM-AKT2 fusion protein on expression of key genes and on EOC proliferation. We believe that reveling the mechanism of this fusion protein will help identify new biomarkers and possibly targeted therapy for ovarian cancer.